A Thioacetal Photocage Designed for Dual Release: Application in the Quantitation of Therapeutic Release by Synchronous Reporter Decaging. (30th November 2016) - Wong, Pamela T.; Tang, Shengzhuang; Cannon, Jayme; Mukherjee, Jhindan; Isham, Danielle; Gam, Kristina; Payne, Michael; Yanik, Sean A.; Baker, James R.; Choi, Seok Ki
Abstract: Despite the immense potential of existing photocaging technology, its application is limited by the paucity of advanced caging tools. Here, we report on the design of a novel thioacetal ortho ‐nitrobenzaldehyde (TNB) dual arm photocage that enabled control of the simultaneous release of two payloads linked to a single TNB unit. By using this cage, which was prepared in a single step from commercial 6‐nitroverataldehyde, three drug–fluorophore conjugates were synthesized: Taxol‐TNB‐fluorescein, Taxol‐TNB‐coumarin, and doxorubicin‐TNB‐coumarin, and long‐wavelength UVA light‐triggered release experiments demonstrated that dual payload release occurred with rapid decay kinetics for each conjugate. In cell‐based assays performed in vitro, dual release could also be controlled by UV exposure, resulting in increased cellular fluorescence and cytotoxicity with potency equal to that of unmodified drug towards the KB carcinoma cell line. The extent of such dual release was quantifiable by reporter fluorescence measured in situ and was found to correlate with the extent of cytotoxicity. Thus, this novel dual arm cage strategy provides a valuable tool that enables both active control and real‐time monitoring of drug activation at the delivery site. Abstract : Binary photocage : An ortho ‐nitrobenzaldehyde‐derived dual arm photocage was developed for real‐time monitoring of the simultaneous release of two payloads linked to a single cage unit. Light‐controlled uncaging of the drug–fluorophore conjugate resulted in increased cellular fluorescence, which was found to correlate with cytotoxicity.